HIV - Livingstone S. Luboobi; Joseph Y.T. Mugisha (Fondazione Eni Enrico Mattei (FEEM), 2005)
Three-quarters of the worlds AIDS population lives in Sub-Saharan Africa; most have no access to lifesaving drugs, testing facilities or even basic preventative health care. One of the major factors inhibiting medical professionals in Africa from treating this disease is the inability to access vast areas of the continent with adequately equipped medical facilities. To meet this need, Architecture for Humanity challenged the worlds architects and health care professionals to submit designs for a mobile HIV/AIDS health clinic. The pandemic is changing the demographic structure of Africa and wiping out life expectancy gains. Indeed, in many African countries, life expectancy is dropping from more than 60 years to around 45 years or even less. In this paper, we highlight the uniqueness of factors associated with HIV/AIDS pandemic in Africa and present its impact and challenges.
Keywords: I18; J11; 330; HIV/AIDS; Africa; AIDS; Afrika